2007
DOI: 10.1002/bip.20789
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self‐assembly composition on the alternate interfacial electron transfer for electrostatically immobilized cytochrome c

Abstract: We report on the effects of self-assembled monolayer (SAM) dilution and thickness on the electron transfer (ET) event for cytochrome c (CytC) electrostatically immobilized on carboxyl terminated groups. We observed biphasic kinetic behavior for a logarithmic dependence of the rate constant on the SAM carbon number (ET distance) within the series of mixed SAMs of C(5)COOH/C(2)OH, C(10)COOH/C(6)OH, and C(15)COOH/C(11)OH that is in overall similar to that found earlier for the undiluted SAM assemblies. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…Previous studies that exploited SAM-coated electrodes revealed two kinds of phenomenological behavior (17)(18)(19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31). For the case of thicker SAMs (long-range ET), these studies showed an exponential decay of k et with the SAM thickness (that is a part of the ET distance, R e ); in accordance with the nonadiabatic ET (tunneling) theory (1, 3, 17-22, 24-32, 46-50):…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Previous studies that exploited SAM-coated electrodes revealed two kinds of phenomenological behavior (17)(18)(19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31). For the case of thicker SAMs (long-range ET), these studies showed an exponential decay of k et with the SAM thickness (that is a part of the ET distance, R e ); in accordance with the nonadiabatic ET (tunneling) theory (1, 3, 17-22, 24-32, 46-50):…”
supporting
confidence: 74%
“…The use of bioelectrochemical tunneling junctions, such as self-assembled monolayer (SAM) films of variable composition and thickness on metal electrodes, with redox proteins immobilized at the solution interface (or freely diffusing to the SAM terminal groups) have been shown to provide an assembly with well-defined and variable control parameters. As such, these assemblies are well suited for fundamental studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and offer promise for versatile nanotechnology applications (32,33). On the basis of earlier fundamental efforts, this work studies ET between a Au electrode that is coated with a SAM alkanethiol film of variable thickness and a "model" biomolecular target, the blue copper protein, Az, from Pseudomonas aeruginosa that is immobilized through hydrophobic interactions onto the SAM.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…two orders of magnitude less than those achieved at similarly modified planar gold electrodes. 54 The lower rate constants may arise from changes in the composition of the SAM, which have been observed with FcHxSH. Such changes can significantly change the faradaic reponse of the protein.…”
Section: Voltammetric Characterization Of Cyt C Immobilized On Planarmentioning
confidence: 98%